2020
DOI: 10.31933/dijms.v1i5.285
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Effect of Capr, Dar, Roa and Size on Tax Avoidance

Abstract: This study aimed to identify the effect of the independent variable capital intensity (CAPR), return on assets (ROA), debt to asset ratio (DAR), and the size of the company (SIZE) on tax avoidance (CETR) as dependent variable. This study tested using multiple linear regression analysis with the SPSS 25 program with a causality and comparative approach using cross sectional data. The results of the study in 2015 showed that the capital intensity and debt to asset ratio does not affect on tax avoidance, while re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Two different measures which are regularly mentioned associated with financial institution overall performance this is regularly used (ROA) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Two different measures which are regularly mentioned associated with financial institution overall performance this is regularly used (ROA) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the background and theoretical study above, the researcher determines the conceptual framework as follows: Based on the conceptual above, there are other factors that influence the Stock Price, including: 1) Capital: (Wulandari & Badjra, 2019), (Prihatminingtyas, 2019), (Noekent, 2018), (Akbar & Hakiman Thamrin, 2020), (Samudra & Husnah, 2016), (Dinova & Herawati, 2020). 2) Total Assets: (Rani et al, 2015), (Satria & Hatta, 2017), (Hasanah & Enggariyanto, 2018).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Financial ratios that describe the company's internal conditions can also affect the level of compliance. Compliance is proven to be affected by profitability (Kasim & Saad, 2019;Mocanu et al, 2021;Akbar & Thamrin, 2020;Oboh & Nosa, 2021;Dewinta & Setiawan, 2016;Dewi & Noviari, 2017;Syaifullah & Ramdany, 2020). Liquidity is also a determinant that affects compliance (Abdullah, 2020;Budianti & Curry, 2018;Batista et al, 2012).…”
Section: Source: Modified From Directorate Of Customs and Excise Audi...mentioning
confidence: 99%
“…The company will try to make efficiency through the use of various facilities to reduce the customs payment by paying attention to compliance with existing regulations. Kasim & Saad (2019), Mocanu et al (2021) and Akbar & Thamrin (2020) have conducted research and concluded that the company's characteristics in the form of profitability have a significant effect on tax avoidance. In other words, the company's profitability has a significant positive effect on the level of company compliance.…”
Section: Source: Modified From Widdowson (2020)mentioning
confidence: 99%